Eksistensi Partai Politik Dalam Penyelenggaraan Pemilu Legislatif Di Indonesia Pasca Putusan Penerapan Sistem Proporsional Terbuka - Abd Hannan (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2023)
Abstract: This study focuses on examining the existence of political parties in the implementation of legislative elections in Indonesia, especially the relationship between political parties and candidates or candidates, the relationship between political parties and the people (voters) after the decision of the constitutional court on the arrangement of an open proportional system in legislative elections in Indonesia. This study is a literature study conducted based on the type of qualitative research. The data used is secondary data in the form of literature sources that have a correlation with the main research problems. After analyzing field data using the perspective of political sociology and legal sociology theory, this study found findings that the decision of the Constitutional Court to maintain an open proportional election system did not bring much change to the existence of political parties. The position and status of political parties remain the same as in the previous legislative elections. Based on empirical experience, election arrangements with an open proportional system, despite a number of advantages and disadvantages, the potential for weakening the existence of political parties in future elections is still wide open. In particular, the weakening of party roles and functions such as the functions of political education, political recruitment, political communication, political socialization, and political participation. This is because in setting elections with an open system, the bargaining power and control of political parties is reduced because they no longer hold a vital position as a major player, but instead have shifted their role as merely a political vehicle.Abstrak: Studi ini fokus mengkaji eksistensi partai politik dalam penyelenggaraan pemilu legislatif di Indonesia, terkhusus hubungan antara partai politik dan kandidat atau calon, hubungan antara partai politik dan rakyat (pemilih) pasca-putusan mahkamah konstitusi terhadap pengaturan sistem proporsional terbuka dalam pemilu legislatif di Indonesia. Kajian ini merupakan studi kepustakaan yang dilakukan berdasarkan jenis penelitian kualitatif. Data yang digunakan adalah data sekunder berupa sumber literatur yang memiliki korelasi dengan permasalahan utama penelitian. Setelah melakukan analisa data lapangan dengan menggunakan perspektif teori sosiologi politik dan sosiologi hukum, studi ini mendapati temuan bahwa putusan lembaga Mahkamah Konstitusi mempertahankan pemilu sistem proporsional terbuka tidak membawa perubahan banyak bagi eksistensi partai politik. Posisi dan kedudukan partai politik tetap sama seperti halnya gelaran pemilu legislatif sebelumnya. Berdasarkan pengalaman empiris, pengaturan pemilu dengan sistem proporsional terbuka, terlepas dari sejumlah keunggulan dan kelebihannya, potensi melemahnya eksistensi partai politik dalam gelaran pemilu ke depan masih terbuka lebar. Khususnya pelemahan terhadap peran dan fungsi kepartaian semisal fungsi pendidikan politik, rekrutmen politik, komunikasi politik, sosialisasi politik, dan partisipasi politik. Demikian karena dalam pengaturan pemilu dengan sistem terbuka, daya tawar dan kontrol parpol berkurang karena dirinya tidak lagi memegang posisi vital sebagai pemain utama, melainkan telah beralih peran sebagai kendaraan politik semata.